Determinants of Acute Respiratory Infections Among Child Under Five Years in Surabaya - Kinanthi, Citra Anggun; Notobroto, Hari Basuki; Martini, Santi (Health Notions, 2018)
Acute respiratory infection (ARI) are leading causes of mortality and morbidity in children under the age of five in developing countries. The incidence and prevalence of ARI are a great burden in low and middle-income countries in comparison to high income ARI. The main objective of the study was to identify determinants of acute respiratory infections among child under five years in Surabaya. This is a case-control study conducted in Public Health Center (Puskesmas) in Surabaya. Data were collected by interviewing community with 1: 1 sample that consists of 66 sample of the case and 66 sample of control. Result: 34.1% was age group <24 months, 14.4% was low birth weight, 57.6% was without exclusive breastfeeding, 22.7% was not measles immunization. The determinant of acute respiratory infections among child under five years was exclusive breastfeeding which the significant showed consecutively p=0.582 (OR=4.163). The Community education programs should focus on addressing specific issues to identify the respiratory illness, simple case management, proper immunization practices, breastfeeding of infants.    Keywords: Child under five years, Acute respiratory infections, Determinants